Identification of a Novel Densovirus in Aphid, and Uncovering the Possible Antiviral Process During Its Infection - Li, Tong; Li, Haichao; Wu, Yuqing; Li, Shaojian; Yuan, Guohui; Xu, Pengjun (Frontiers in Immunology, 2022)
Densoviruses (DVs) are single-stranded DNA viruses and exclusively happen in invertebrates. Most of DVs reported in insects are pathogenic to their native hosts, however, no pathogenic effect of them has been examined in vertebrates. Hence, DVs are the potential agents used in pest managements. Aphids are the primary vectors of plant viruses. In this study, we identified a novel DV in Chinese Sitobion miscanthi population, provisionally named “Sitobion miscanthi densovirus” (SmDV). Taxonomically, SmDV belongs to genus Hemiambidensovirus. In S. miscanthi, SmDV is hosted in diverse cells and can be horizontally transmitted via wheat feeding. Subject to SmDV, aphids activate their intrinsic antiviral autophagy pathway. Grouped with ascorbate and aldarate metabolism, chlorophyll metabolism, p450 related drug metabolism, and retinoid metabolism, aphids form a complex immune network response to the infection of SmDV. Obviously, it works as elder aphids still alive even they contain the highest examined concentration of SmDV. This study provides a foundation for the identifications of novel DVs, and further improves the understanding of the molecular interactions between insects and DVs.